THEORETICAL FOUNDATIONS OF THE USE OF DIDACTIC MATERIALS IN THE EDUCATIONAL PROCESS (International journal of artificial intelligence, 2025)
Currently, conducting classes in accordance with the requirements of world educational standards means organizing classes based on pedagogical technologies. Therefore, pedagogical technologies as a discipline are deeply embedded in the education system, starting from the higher education system, because the implementation of innovative educational technologies in the pedagogical process through a technological approach to education is showing its effectiveness. Therefore, providing students with knowledge based on new and latest pedagogical technologies and training them as mature individuals on this basis is a requirement of today. In the context of accelerating scientific and technological progress, didactic materials are gaining special importance.